STRATEGI KEBERHASILAN USAHA HOME INDUSTRY SEPATU DALAM MEMBERDAYAKAN MASYARAKAT - Sarah Fauziah Audina; Muhtadi Muhtadi (JURNAL AGRIBISNIS TERPADU, 2019)
Many companies in Indonesia are competing to become superior companies and they have to fight hard to keep their business going. This study aims to determine what strategies are used to maintain its business and see if the presence of home industry shoes is able to empower the surrounding community. Through the process of interviewing and observation, it can be seen that the strategy of business sustainability using assets nirwujud sustainable business. The results showed that the strategy undertaken by shoe home industry owned by Mr. Haryono able to survive until now by applying the strategy of micro and mezzo aras. As well as the stages of empowerment as well as through the Business Sustainability Indicators where the business sustainability index is divided into three parts namely, (1) the index of business sustainability on the ecological dimension, (2) the index of business sustainability on the economic dimension and, (3) the index of business sustainability on the social dimension. Mr. Haryono has also succeeded in empowering the surrounding community by changing their mindset by providing motivation so that some of their former employees are also able to capitalize the business with the skills acquired during work in the home industry of Mr. Haryono's shoes.